2021
DOI: 10.1155/2021/7117613
|View full text |Cite
|
Sign up to set email alerts
|

BDNF Genetic Variant and Its Genotypic Fluctuation in Major Depressive Disorder

Abstract: Major depressive disorder (MDD) still has an unknown etiology and mechanisms. Many studies have been conducted seeking to associate and understand the connection of different genetic variants to this disease. Researchers have extensively studied the brain-derived neurotrophic factor (BDNF) Val66Met genetic variant in MDD; yet, their findings remain inconsistent. This systematic review sought to verify the GG (Val/Val) genotype frequency fluctuation in different populations with MDD. For this, we searched in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 80 publications
(161 reference statements)
0
3
0
Order By: Relevance
“…Especially, the single-nucleotide polymorphism BDNF Val 66 Met, which causes a valine (Val) to methionine (Met) substitution at codon 66 of the BDNF protein, is of high interest because of its known influence on hippocampal functions [ 16 ]. It has also been associated with AD and depression in the past [ 20 , 21 ]. Studies in rodents and humans suggested that carriers of the BDNF Met allele show lower hippocampal volumes [ 19 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the single-nucleotide polymorphism BDNF Val 66 Met, which causes a valine (Val) to methionine (Met) substitution at codon 66 of the BDNF protein, is of high interest because of its known influence on hippocampal functions [ 16 ]. It has also been associated with AD and depression in the past [ 20 , 21 ]. Studies in rodents and humans suggested that carriers of the BDNF Met allele show lower hippocampal volumes [ 19 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depression rates are on the rise globally. According to the World Health Organization (WHO), the number of MDD cases grew by 18.4% from 2005 to 2015 [ 1 ], though this increase could also be attributed to population growth and/or gradually decreasing stigmatization surrounding mental illness [ 3 ]. In the first year of the COVID-19 pandemic, rates of common conditions, such as depression and anxiety, went up by more than 25% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly examined BDNF single nucleotide polymorphism (SNP) produces a valine-to-methionine substitution at codon 66 (Val66Met; rs6265), with the Met allele associated with reduced activity-dependent secretion of BDNF (Egan et al, 2003). While hundreds of studies have examined the association between rs6265 (and other BDNF SNPs) and brain-related conditions, results have been mixed, as is observed in many complex phenotypes (Ahmed et al, 2015; Ferreira Fratelli et al, 2021; Pereira et al, 2018). Also, when examined in consortium studies with very large sample sizes, some of the BDNF associations previously seen in small candidate gene studies have not replicated (Border et al, 2019; Johnson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%